What do we know about interactive computer-assisted screening for intimate partner violence and control in clinical settings? A systematic review (Italian Journal of Public Health, 2010)
Background: Intimate partner violence is a major public health issue, particularly among women. Abused women experience many acute and chronic health consequences resulting in frequent healthcare visits. There exists a system-level opportunity to intervene, yet abused women refrain from spontaneous disclosure of their experiences of victimization due to embarrassment. Meanwhile providers often fail to ask due to lack of time, priority of acute medical problems and discomfort. Missed opportunities to detect intimate partner violence and control (IPVC) can be availed by computer-assisted interactive screening.Aim: The purpose of this paper is to critically review current scientific knowledge on the use of enhanced Web 2.0 interactive computer-assisted screening for IPVC in clinical settings.Methods: A systematic review of peer-reviewed published literature was conducted using Medline and PsychInfo data bases from 1996 to 2010. Eligibility criteria were applied to the identified records. Additional studies were identified by searching reference list and contacting authors. Eight eligible studies were appraised for the study characteristics and IPVC related outcomes for the process-of-care, patient, and provider.Results: The selected studies (descriptive, randomized trial, and qualitative) were conducted in the emergency and family medicine settings on two programs of research which used similar interactive computer screen, Promote Health. The reviewed evidence supports the effectiveness of computer screening for improving provider-patient communication on IPVC in both settings and compromised mental health in family medicine. However the management of detected cases of IPVC by time-pressed frontline clinicians needs a more supportive environment. The need for such system-level support is greater for the emergency setting.Conclusions: The use of computer-assisted screening in similar settings can enhance the detection and disclosure of IPVC, although a coordinated multiservice response is needed to address it comprehensively. Future studies should examine the development of a coordinated response and the role of context on the success or failure of such program.
Keywords: Partner violence; emergency department; family medicine; computer screen; review